Paracetamol (acetaminophen) protein adduct concentrations during therapeutic dosing. (14th January 2016) - Heard, Kennon; Green, Jody L.; Anderson, Victoria; Bucher‐Bartelson, Becki; Dart, Richard C.
Abstract : Background: Paracetamol protein adducts (PPA) are a biomarker of paracetamol exposure. PPA are quantified as paracetamol–cysteine (APAP‐CYS), and concentrations above 1.1 μmol l –1 have been suggested as a marker of paracetamol‐induced hepatotoxicity. However, there is little information on the range of concentrations observed during prolonged therapeutic dosing. Aim: The aim of the present study was to describe the concentration of PPA in the serum of subjects taking therapeutic doses of paracetamol for at least 16 days. Methods: Preplanned secondary aim of a prospective randomized controlled (placebo vs . 4g day –1 paracetamol) trial. We measured subjects' serum PPA concentrations every 3 days for a minimum of 16 days. We also measured concentrations on study days 1–3 and 16–25 in subsets of patients. PPA were quantified as APAP‐CYS after gel filtration and protein digestion using liquid chromatography/mass spectrometry. RESULTS: Ninety per cent of subjects had detectable PPA after five doses. Median APAP‐CYS concentrations in paracetamol‐treated subjects increased to a plateau of 0.1 μmol l –1 on day 7, where they remained. The highest concentration measured was 1.1 μmol l –1 and two subjects never had detectable PPA levels. PPA were detected in the serum of 78% of subjects 9 days after their final dose. Conclusions: PPA are detectable in the vast majority of subjects taking therapeutic doses of paracetamol. While most have concentrations well below the threshold associated with hepatotoxicity, concentrations may approach 1.1 μmol l –1 in rare cases. Adducts are detectable after a few doses and can persist for over a week after dosing is stopped.